High-strength and tough bioactive Mg-doped hydroxyapatite bioceramics with oriented microchannels. Issue 10 (15th May 2022) - Zhao, Xueni; Wei, Sensen; Yang, Zhi; Yang, Pinglin; Liu, Ao
Abstract: Mg-doped hydroxyapatite (MH) with oriented microchannels was prepared by hot-pressing sintering and pore-forming heat treatment using continuous carbon fibres (CFs) as the pore-forming agent to achieve balanced mechanical and biological properties. The proportion of MH and (Ca, Mg)3 (PO4 )2 in the microporous bioceramic with inter-microchannel spacing of 400 μm obtained by sintering at 900 °C (900-2P-MH) was 43.9/56.1 (wt%), which could promote degradation. The compressive strength of the MH bioceramics containing oriented microchannels with a suitable pore size (5–14 μm) did not decrease, but increased in comparison with that of a dense MH sample without microchannels. In particular, the compression strength of the MH bioceramic with oriented microchannels formed using single CF units was 53.31% higher than that of the dense ones. The fracture toughness of the MH bioceramics with oriented microchannels increased to 177.42% of that of the dense ones. The strengthening and toughening mechanism includes contributions from the combination of heating and pressing, uniform distribution of microchannels, and in situ formation of continuous micro/nano-MH ceramic tubes. Moreover, the microchannel-containing MH showed noticeably improved apatite mineralisation in simulated body fluid (SBF). Analysis of the rat tibial bone defect model revealed that the relative bone volumes in the cases of the dense MH without microchannels and the MH with microchannels increased by 23.18 and 40.14%, respectively, compared with that of hydroxyapatite. Furthermore, the MH bioceramics with oriented microchannels displayed a moderate reduction in strength owing to degradation after 8 weeks of implantation. The satisfactory osteogenic properties and degradability of the microporous bioceramic can be attributed to Mg 2+ doping and oriented microchannels. Highlights: A new and effective strengthening and toughening method was developed for ceramic-matrix composites. Oriented-microchannel-containing Mg-doped hydroxyapatite (MH) with balanced mechanical and biological properties was constructed using continuous CFs as the pore-forming agent. Continuous micro/nano ceramic tubes were formed in situ in the oriented microchannels of MH. Compression strength of MH bioceramics with oriented microchannels was 53.31% higher than that of MH without microchannels. Fracture toughness of MH bioceramics with oriented microchannels increased to 177.42% of that of MH without microchannels.